Zygmunt Bauman: uma biobibliografia e possíveis diálogos com a educação - Manfio, João Nicodemos Martins (2017)
This thesis analyse the biobibliography of Zygmunt Bauman, sociologist who made the idea of liquid modernity universal. Through the analysis of the phases of his thought, with the help of the interpreters of his work Aguiluz-Ibargüen (2009), Beilharz (2001), Smith (1999), Béjar (2005) and Tester (2004) proved to be essentially concerned thinker with the daily lives of people in their struggle for survival and defender of dialogue between the different. The possibility of an encounter between the author and other important educational thinkers such as Freire (1996), Pineau (2003) and Morin (2015) has been built from the observation that education faces institutional crisis due to the transformations in liquid modernity. From the identification with his thought was made reflection on the personal course from the primary school to the higher teaching highlighting vicissitudes and conquests. Personal interviews were conducted with Bauman that support the understanding of his teachings for the convergence between Social Sciences and Education